M-Polynomials and Degree-Based Topological Indices of the Molecule Copper(I) Oxide - Faryal Chaudhry; Iqra Shoukat; Deeba Afzal; Choonkil Park; Murat Cancan; Mohammad Reza Farahani (Journal of Chemistry)
Topological indices are numerical parameters used to study the physical and chemical residences of compounds. Degree-based topological indices have been studied extensively and can be correlated with many properties of the understudy compounds. In the factors of degree-based topological indices, M-polynomial played an important role. In this paper, we derived closed formulas for some well-known degree-based topological indices like first and second Zagreb indices, the modified Zagreb index, the symmetric division index, the harmonic index, the Randić index and inverse Randić index, and the augmented Zagreb index using calculus.